A new species of Axymyiidae (Diptera) from western North America and a key to the Nearctic species - Fitzgerald, Scott J.; Wood, D. Monty (Zootaxa, 2014)
Adult, pupal and larval stages of the western Nearctic axymyiid, Protaxymyia thuja Fitzgerald and Wood n. sp., are described. The generic placement of this taxon is discussed in the context of the world axymyiid fauna and a key to differentiate all known life stages of Nearctic axymyiids is provided.